USE OF NITROUS OXIDE IN ELDERLY PATIENTS WITH COMORBIDITIES: AN INTEGRATIVE REVIEW - Barroso, Ana Beatriz Nunes Santos e Silva; Moreira, Joyce Costa (Seven Editora, 2026)
Nitrous oxide (N₂O) is widely used for conscious sedation in outpatient settings, particularly in dentistry, due to its favorable pharmacological profile, characterized by rapid onset of action, easy titration, and predictable recovery. Its use has been consolidated as an effective strategy for anxiety control, improvement of patient cooperation, and facilitation of clinical procedures with greater comfort and safety. In this context, its application in elderly patients with comorbidities represents a relevant alternative, especially in scenarios that require less invasive approaches and greater physiological stability. This study aimed to evaluate the safety and clinical applicability of N₂O for conscious sedation in this population through an integrative literature review. The literature search was conducted in PubMed/MEDLINE, SciELO, and ScienceDirect databases using descriptors related to “nitrous oxide,” “conscious sedation,” “elderly,” and “comorbidities,” and a total of 12 scientific articles were included. The findings indicate that N₂O presents a consistent safety profile, particularly when used in controlled concentrations and under appropriate monitoring, with clinical risks more strongly associated with patients’ baseline conditions rather than the agent itself. Metabolic effects, especially those related to vitamin B12, should be considered in a contextualized manner, particularly in individuals with pre-existing conditions, and do not constitute an absolute limitation to its use. In addition, advantages such as maintenance of spontaneous ventilation, rapid recovery, and broad clinical applicability are highlighted. In conclusion, N₂O represents a viable, safe, and effective strategy for conscious sedation in elderly patients with comorbidities, provided it is used judiciously, with individualized assessment and structured clinical protocols.